Optimal active and reactive nodal power requirements towards loss minimization under reverse power flow constraint defining DG type. (June 2016) - Bouhouras, Aggelos S.; Sgouras, Kallisthenis I.; Gkaidatzis, Paschalis A.; Labridis, Dimitris P.
Highlights: The siting and sizing of DG units in DNs is examined under an innovative perspective. A Local PSO (LPSO) variant algorithm is utilized for the problem. The algorithm provides the optimal number of nodes to host DG units. Moreover, the optimal active and reactive power of each node is resulted. The solution is not biased since all variables are optimized simultaneously. Abstract: In this paper a novel approach regarding the optimal penetration of Distributed Generation (DG) in Distribution Networks (DNs) towards loss minimization is proposed. More specific, a Local Particle Swarm Optimization (PSO) variant algorithm is developed in order to define the optimal active and reactive power generation and/or consumption requirements for the optimal number and location of nodes that yield loss minimization. Thus, the proposed approach provides the optimal number, siting and sizing of DGs altogether. In addition, based on the optimal power requirements of the resulted nodes, a combination of potential DG types to be installed is recommended. The proposed objective function in this paper is also innovative since it embeds the constraint of reverse power flow to the slack bus by the formation of a new penalty term. The proposed methodology is applied to 30 and 33 bus systems. The results indicate the optimal number, locations, and capacity of DG units, which were calculated simultaneously. Finally, the impact of the predefined amount of permissible reverse power flow to the optimal solution is also examined through two scenarios: the first considers zero reverse power flow and the second unlimited reverse power flow.